Overcoming barriers to self-management: The person-centred diabetes foot behavioural agreement. (March 2019) - Bullen, Benjamin; Young, Matthew; McArdle, Carla; Ellis, Mairghread
Highlights: 98% of diabetes management is self-care. Effective self-foot care can prevent diabetes foot disease. Self-foot care requires functional, interactive and critical health literacy skills. Behavioural agreements delineate, prescribe and support individual responsibilities. Abstract: Objective: Behavioural agreements have been proposed as a clinical strategy for improving concordance with diabetes foot self-management practices, both for individuals 'At-risk' of, and with active, diabetes foot disease. This narrative review sought to explore the potential supportive role of person-centred diabetes foot behavioural agreements in promoting protective foot self-management behaviours among 'At-risk' individuals. Conclusions: Healthcare professionals (HCPs) involved in diabetes foot risk stratification and management dedicate considerable time, effort and resources to the prevention of diabetic foot ulcers (DFU) and lower extremity amputation (LEA) and are uniquely placed to deliver person-centred diabetes self-management education and support (DSMES) interventions. Written, verbal and non-verbal agreements are consistent with a wider global move toward DSMES approaches, respectful of people's preferences, and supporting them to undertake protective self-care behaviours. Practice implications: It is theorised that clear communication of the roles of the person with diabetes, their family or carers and HCPs may improve concordance with self-management behaviours. Rather than a punitive measure or means of facilitating discharge of 'non-concordant' individuals, person-centred behavioural agreements should be framed positively, as a means of delineating, prescribing and supporting individual diabetes foot-care responsibilities. This is an area worthy of further research.